Investigating snowpack volumes and icing dynamics in the moraine of an Arctic catchment using UAV photogrammetry. (5th December 2017) - Bernard, Éric; Friedt, J. M.; Tolle, F.; Griselin, M.; Marlin, Ch.; Prokop, A.
Abstract: Methods for assessing the contribution of the proglacial moraine into the water budget of an Arctic glacier are investigated. High spatial resolution elevation models at different seasons are needed to estimate the volume of ice and snow accumulated during winter in this part of the catchment basin and released into rivers during the melting season. Lidar currently provides the highest resolution for the generation of digital elevation models (DEMs). This paper considers the complementary use of a commercial off‐the‐shelf DJI Phantom 3 Professional unmanned aerial vehicle (UAV) for acquiring aerial photography, combined with structure‐from‐motion (SfM) analysis, for DEM computation. DEM differences between datasets acquired in April (maximum snow accumulation) and September (minimum snow cover) yield a volume difference attributed either to snow cover or icing formation. Repeated measurements over a short period highlight the processes of snow‐cover storage in the moraine and melting dynamics.